2017
DOI: 10.1002/cssc.201601675
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electrochemical Reduction of CO2 for Future Use in Secondary Microbial Electrochemical Technologies

Abstract: The fluctuation and decentralization of renewable energy have triggered the search for respective energy storage and utilization. At the same time, a sustainable bioeconomy calls for the exploitation of CO as feedstock. Secondary microbial electrochemical technologies (METs) allow both challenges to be tackled because the electrochemical reduction of CO can be coupled with microbial synthesis. Because this combination creates special challenges, the electrochemical reduction of CO was investigated under condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 85 publications
2
36
1
1
Order By: Relevance
“…The Ta fel slope wasa pproximately 110mVdec À1 for the Ni@N-C catalyst (Figure 2b). [18,45] Therefore, before coupling with the biosyn-thetic process, the Ni@N-C catalytic performance was evaluated in minimal mediuma nd Pt/C was used as ac omparison. It hasb een reported that the various ions in the bacterial growth medium could seriously affect the activity sites on the electrocatalysts, decreasing selectivity and stability ( Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ta fel slope wasa pproximately 110mVdec À1 for the Ni@N-C catalyst (Figure 2b). [18,45] Therefore, before coupling with the biosyn-thetic process, the Ni@N-C catalytic performance was evaluated in minimal mediuma nd Pt/C was used as ac omparison. It hasb een reported that the various ions in the bacterial growth medium could seriously affect the activity sites on the electrocatalysts, decreasing selectivity and stability ( Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…It hasb een reported that the various ions in the bacterial growth medium could seriously affect the activity sites on the electrocatalysts, decreasing selectivity and stability ( Figure S4). [18,45] Therefore, before coupling with the biosyn-thetic process, the Ni@N-C catalytic performance was evaluated in minimal mediuma nd Pt/C was used as ac omparison. The LSV results reveal that the overpotential of HER for the Ni@N-Cw as about 150 mV,w hich was lower than that obtained in the 1.0 m KOH ( % 250 mV).…”
Section: Resultsmentioning
confidence: 99%
“…Using electrical power to provide feedstock for bioconversions is the essence of power-to-X-technologies.M ost commonly,H 2 from water electrolysis is considered. [29] However,C 1 -compounds like formate [30,31] or C 2 -compounds [32][33][34][35][36] or CH 4 [37] can also be provided using electric energy and CO 2 . Electrochemical oxygen evolution also has to be mentioned, although it plays an only minor role,sof ar.…”
Section: Providing Chemical Feedstockmentioning
confidence: 99%
“…[31] In this line, the utilization of an in situ coupling of the electrochemical reduction of CO 2 to formate with formate serving as a carbon and energy source for biosynthesis, e. g. of alcohols, has been shown. [32,33] A bioelectrorefinery that couples a first microbial step to a subsequent abiotic organic electrosynthesis is the conversion of muconic acid (see Scheme 3) gained from glucose fermentation using a genetically engineered S. cerevisae. [26] Also, the production of methylsuccinic acid from glucose via microbial production of the intermediate itaconic acid using Aspergillus terreus DSM 23081 that is electrochemically converted in situ (Scheme 6) has been demonstrated.…”
Section: The Electrobiorefinery Conceptmentioning
confidence: 99%